Agriculture and undernutrition - Headey, Derek D.; Masters, William A. (International Food Policy Research Institute, 2021)
First, we typically use the term agriculture to mean the farm production of crop and livestock commodities; agribusiness to mean commercial suppliers of farm inputs and wholesale purchasers of farm commodities; food markets to mean storage, shipment, and transformation of food into final products including packaged foods and meals away from home; and as a shorthand for any public sector or philanthropic intervention or program that aims to alter these activities. These are all interrelated influences on what we will call livelihoods, meaning all of a household’s activities, including both agriculture and nonfarm work. Putting these pieces together, the chapter will focus on agricultural and food systems, meaning the aggregate outcome of interactions between these components at the scale of an entire village, region, country, or the world as a whole. Second, this chapter focuses on undernutrition-defined as insufficient intake of nutrients and healthy foods relative to biological needs, and the resulting deficiencies such as anemia and failure to achieve a child’s genetic potential such as linear growth-rather than problems linked to excessive intake of total energy, salt, and harmful foods that lead to obesity and diet-related diseases such as hypertension and diabetes. The two types of malnu-trition are connected, as many people who suffer from dietary insufficiencies in some dimensions also have excesses in others (for example, stunting in childhood followed by obesity in later life, or ongoing micronutrient deficien-cies during weight gain), but excessive intake of harmful foods is less likely than dietary insufficiency to be caused by agricultural production and sup-ply constraints. As this chapter will show, agricultural change can raise food intake where deficiencies are most widespread, while excesses that lead to obe-sity and diet-related disease are more closely tied to nonfarm activity, market conditions, and food demand. Excessive intake clearly links back to agricul-ture through demand for ingredients in unhealthy foods such as sugar and other carbohydrates, but we would hypothesize a fundamental asymmetry in agriculture-nutrition linkages: improving agricultural production can help poor people fill deficiencies, especially for children in poor rural households, but after intake has risen, attempting to use agriculture against obesity can be like pushing on a string.